High Frequency Micropropagation of Aloe vera L. Burm. f. as a Low Cost Option Towards Commercialization (Plant Tissue Culture and Biotechnology, 2010)
An efficient micropropagation protocol has been developed using shoot apical meristem as explants in a high barbaloin content 'bitter' cultivar of Aloe vera L. The protocol involves induction, multiplication and in vitro rooting of the regenerated shoots and their acclimation under ex vitro conditions. 35.5 µM BAP and 9.8 µM IBA in combination with 81.4 µM adenine sulphate proved optimum for shoot bud induction. Combination of 8.87 µM BAP and 2.46 µM IBA produced highest number of shoot buds (22.0 ± 0.14) and enhanced bud proliferation within one - two weeks after first subculture. For induction of in vitro rooting, Aloe gel as an alternative to conventional rooting medium used for the first time resulted in 100% rooting and highest number of roots per culture (10.90 ± 0.17). The plantlets were successfully hardened. Cent per cent plants survived in the field condition. Chromosomal analysis of the regenerated plantlets established a stable germplasm with 2n = 14 bimodal chromosomes. The cost effectiveness and economic viability of the protocol has also been evaluated. Key words: Aloe vera, bitter cultivar, micropropagation, cost analysis D.O.I. 10.3329/ptcb.v20i1.5962 Plant Tissue Cult. & Biotech. 20(1): 29-35, 2010 (June)